Systematic reviews on interventions for COVID-19 have rarely graded the certainty of the evidence - Martimbianco, Ana Luiza Cabrera; Pacheco, Rafael Leite; Latorraca, Carolina de Oliveira Cruz; Ferreira, Raphael Einsfeld Simões; Riera, Rachel (São Paulo Medical Journal, 2021)
BACKGROUND: Numerous systematic reviews on coronavirus disease-19 (COVID-19) treatment have been developed to provide syntheses of the large volume of primary studies. However, the methodological quality of most of these reviews is questionable and the results provided may therefore present bias. OBJECTIVE: To investigate how many systematic reviews on the therapeutic or preventive options for COVID-19 assessed the certainty of the evidence through the Grading of Recommendations Assessment, Development and Evaluation (GRADE) approach. METHODS: We conducted a sensitive search in MEDLINE (via PubMed) and included all systematic reviews that assessed any intervention for COVID-19. The systematic reviews included were examined to identify any planned and/or actual assessment using the GRADE approach (or absence thereof ) regarding the certainty of the evidence. RESULTS: We included 177 systematic reviews and found that only 37 (21%; 37/177) assessed and reported the certainty of the evidence using the GRADE approach. This number reduced to 27 (16.2%; 27/167) when Cochrane reviews (n = 10), in which an evaluation using GRADE is mandatory, were excluded. CONCLUSION: Most of the systematic reviews on interventions relating to COVID-19 omitted assessment of the certainty of the evidence. This is a critical methodological omission that must not be overlooked in further research, so as to improve the impact and usefulness of syntheses relating to COVID-19.